The Economic Costs of Tobacco Related Illnesses in Kenya - Daniel Mwai; Gladwell Gathecha; David Njuguna; Jane Ongango; Valerian Mwenda; Dorcas Kiptui; Ann Kendagor; Samuel Cheburet; Shukri Mohamed; Florence Jaguga; Beatrice Mugi; Kennedy Okinda; et al. (Tobacco Use Insights, 2024)
Objective To estimate the economic costs of selected tobacco-related illnesses (TRI) in Kenya in 2022. Research Design and Methods This study was conducted in 2 phases. Phase 1, conducted between 2021 and 2022, entailed conducting a cross-sectional study conducted in 4 national public referral hospitals in Kenya. Patients with cardiovascular disease, cancer, chronic obstructive pulmonary disease, or tuberculosis were interviewed to compute the indirect and direct medical costs related to the illness. Activity-Based Costing approach was used to capture costs for services along the continuum of care pathway. In the second phase, the Tobacco Attributable Factor was used to estimate the direct, indirect, and ultimately economic cost due to tobacco smoking. Results The estimated health care cost attributed to tobacco use in Kenya is US$396,107,364. Among TRIs included in the study, myocardial infarction had the highest health care cost at US$158,687,627, followed by peripheral arterial disease and stroke with health care cost of US$64,723,181 and US$44,746,700 respectively. The main cost driver across all the illnesses is the cost for medication accounting for over 90% of the total health care cost. The productivity losses from the diseases ranged between US$148 to US$360 and accounted for 27% to 48% of the economic costs. The total cost attributable to tobacco use to Kenya’s economy for the selected TRIs was between US$544.74 million and US$756.22 million. Conclusions/interpretation Tobacco related illnesses impose a significant economic burden as reported for direct and indirect costs. These findings underscore the need for strengthened implementation of the provision of the Framework Convention on Tobacco Control and the Tobacco Control Act (2007) to facilitate a reduction in tobacco consumption in the population.